1995
DOI: 10.1113/jphysiol.1995.sp020729
|View full text |Cite
|
Sign up to set email alerts
|

Coding of pulsatile motor output by human muscle afferents during slow finger movements.

Abstract: 1. Impulse activities of thirty‐eight muscle spindle and tendon organ afferents from the finger extensor muscles were recorded in the radial nerve of human subjects while the subjects performed voluntary flexion and extension finger movements at a single metacarpophalangeal joint. 2. The afferent firing was analysed in relation to the 8‐10 Hz discontinuities which previously have been shown to characterize these movements. Spike‐triggered averaging and frequency domain analyses demonstrated that all Ia muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Thus, the M1 activity in question reflects the corrective force increase during the unpredictable weight change and not the total force output. Slow movements of the fingers are characterized by 8 -10 Hz discontinuities (Vallbo and Wessberg, 1993;Wessberg and Vallbo, 1995) to which muscle spindles vigorously respond, and these discontinuities were also observed in this study (Fig. 1, grip force rate profile).…”
Section: Corrective Responses and Their Neural Correlatessupporting
confidence: 81%
“…Thus, the M1 activity in question reflects the corrective force increase during the unpredictable weight change and not the total force output. Slow movements of the fingers are characterized by 8 -10 Hz discontinuities (Vallbo and Wessberg, 1993;Wessberg and Vallbo, 1995) to which muscle spindles vigorously respond, and these discontinuities were also observed in this study (Fig. 1, grip force rate profile).…”
Section: Corrective Responses and Their Neural Correlatessupporting
confidence: 81%
“…Previous studies have reported that CMC was detected at low-frequency band (Wessberg and Vallbo, 1995;Gross et al, 2002) during repetitive slow finger movements. Recent CKC studies also detected the coupling between the cortex and finger at the low-frequency band of repetitive finger movements (Piitulainen et al, 2013a(Piitulainen et al, , 2013bBourguignon et al, 2015).…”
Section: Generator Mechanism Of the Low-cmcmentioning
confidence: 91%
“…Inhibitory pathways converging into group Ia afferents decrease excitatory input to alpha-motoneurons, hence modulating force fluctuations (Yoshitake et al 2004;Shinohara et al 2005). In addition, spatial facilitation between group III and IV muscle afferents and Ib afferents may modulate the sensitivity of muscle tension control by decreased reflex sensitivity in agonist muscles and increased reflex sensitivity in antagonist muscles (Graven-Nielsen et al 2002), modifying the ability of the central nervous system to interpret proprioceptive information needed to precisely control force or position of the limbs (Wessberg and Vallbo 1995). Third, increased synchronization of motor units may have contributed to higher force fluctuations (Yao et al 2000).…”
Section: Multidirectional Force Fluctuations and Painmentioning
confidence: 99%